THE ROLE OF ARTIFICIAL INTELLIGENCE IN ASSESSING SPEAKING (Journal of Uzbekistan’s Development and Research, 2025)
The emergence of Artificial Intelligence (AI) has transformed language learning and assessment, particularly in evaluating speaking skills, one of the most complex and dynamic components of language proficiency. Traditional human-based assessments often lack consistency and scalability, whereas AI-powered systems offer automated, data-driven evaluations that are increasingly sophisticated. This paper explores how AI technologies especially Automatic Speech Recognition (ASR), Natural Language Processing (NLP), and Machine Learning (ML)—are employed to assess speaking. It evaluates the benefits, challenges, and ethical implications of AI use in this context and underscores the importance of combining AI with human expertise to ensure fairness, cultural sensitivity, and pedagogical relevance.